Mindfulness intervention in the management of chronic pain and psychological comorbidity: A meta-analysis - Yan Song; Haixia Lu; Honglin Chen; Guiling Geng; Jing Wang (Elsevier, 2014)
Objective: To review trials on mindfulness intervention for chronic pain in primary care to clarify the evidence base and establish whether mindfulness is an important intervention for relieving pain and improving psychological comorbidity. Methods: We performed a literature search using PubMed, the Cochrane Database, EBSCOhost, Elsevier, Wiley, Springer, and the references of retrieved articles. We included articles written in English and that were published up to January 2012. We found 428 empirical studies, but only eight were included as randomized controlled trials of mindfulness intervention for chronic pain in our meta-analysis. After extracting and synthesizing data from these eight trials, we analyzed the data extracted and synthesized from these eight trials. Results: Compared with control intervention, mindfulness intervention had no specific effect on reducing pain intensity (weighted mean difference 3.24, 95% confidence interval [CI]: −8.92 to 2.45). Mindfulness intervention led to greater improvement in psychological comorbidity with chronic pain, such as depression (weighted mean difference −3.91, 95% CI −5.94 to −2.32) and trait anxiety (weighted mean difference −4.07, 95% CI −4.48 to −3.65). Conclusion: There is insufficient evidence that mindfulness intervention relieves pain intensity. However, it improves depression and trait anxiety in patients with chronic pain. Further research in larger, properly powered, and better-designed studies is warranted.